Search for electroweak production of charginos and neutralinos using leptonic final states in pp collisions at root s=7 TeV - Chatrchyan, S. (2012)
The 2011 dataset of the CMS experiment, consisting of an integrated luminosity of 4.98 fb(-1) of pp collisions at root s = 7 TeV, enables expanded searches for direct electroweak pair production of charginos and neutralinos in supersymmetric models as well as their analogs in other models of new physics. Searches sensitive to such processes, with decays to final states that contain two or more leptons, are presented. Final states with three leptons, with a same-sign lepton pair, and with an opposite-sign lepton pair in conjunction with two jets, are examined. No excesses above the standard model expectations are observed. The results are used in conjunction with previous results on four-lepton final states to exclude a range of chargino and neutralino masses from approximately 200 to 500 GeV in the context of models that assume large branching fractions of charginos and neutralinos to leptons and vector bosons.